2017
DOI: 10.3390/toxins9030087
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Anti-Aflatoxinogenic Activity of Micromeria graeca and Elucidation of Its Molecular Mechanism in Aspergillus flavus

Abstract: Of all the food-contaminating mycotoxins, aflatoxins, and most notably aflatoxin B1 (AFB1), are found to be the most toxic and economically costly. Green farming is striving to replace fungicides and develop natural preventive strategies to minimize crop contamination by these toxic fungal metabolites. In this study, we demonstrated that an aqueous extract of the medicinal plant Micromeria graeca—known as hyssop—completely inhibits aflatoxin production by Aspergillus flavus without reducing fungal growth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 58 publications
2
36
1
Order By: Relevance
“…These strategies range from good agricultural practices to the use of biocontrol agents or natural compounds able to block toxin production [10]. Even if the exact mechanism of action has not yet been completely elucidated, a few studies already demonstrated that some of these natural products can inhibit AFB1 production by a transcriptional down-regulation of the genes involved in AFB1 synthesis [11][12][13][14][15][16][17][18]. Aflatoxins are the product of a complex biosynthesis pathway involving at least 27 enzymatic reactions [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…These strategies range from good agricultural practices to the use of biocontrol agents or natural compounds able to block toxin production [10]. Even if the exact mechanism of action has not yet been completely elucidated, a few studies already demonstrated that some of these natural products can inhibit AFB1 production by a transcriptional down-regulation of the genes involved in AFB1 synthesis [11][12][13][14][15][16][17][18]. Aflatoxins are the product of a complex biosynthesis pathway involving at least 27 enzymatic reactions [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A biocontrol yeast against A. flavus called Wickerhamomyces anomalus was found to inhibit AF production by repressing the activation of the AF biosynthetic pathway cluster [ 17 ]. The extracts from the medicinal plant Micromeria graeca were also reported to restrict AF biosynthesis, without an effect on fungal growth, by the downregulation of aflR and aflS , two activators of the AF gene cluster, and the overexpression of two major global regulators, veA and mtfA [ 18 ]. Zhao et al previously revealed the inhibitory effects of Lactobacillus plantarum on AF biosynthesis using transcriptomic analysis, which showed that the transcriptional levels of genes involved in the AF biosynthetic process were significantly downregulated, while genes related to the synthesis and organization of cell wall polysaccharides were upregulated, which might be related to the impaired effects of L. plantarum on the cellular structure of fungal tissue [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even if several approaches have been developed to limit AFB1's contamination (Wild et al 2015;Jalili, 2015), they remain insufficient to completely avoid mycotoxin contamination thus emphasizing the need to develop new strategies to guarantee food safety. The use of natural products such as spices, plant extracts or essential oils with anti-aflatoxinogenic properties represent a complementary or alternative strategy against mycotoxin contamination (Annis et al, 2000;El Khoury et al, 2017;Holmes et al, 2008;Sakuda et al, 2016). For instance, piperine, a major active component of black and long peppers (Piper nigrum L. and…”
Section: Introductionmentioning
confidence: 99%